A disassembling strategy overcomes the EPR effect and renal clearance dilemma of the multifunctional theranostic nanoparticles for cancer therapy. (March 2019) - Wang, Yanbing; Wang, Zhuo; Xu, Caina; Tian, Huayu; Chen, Xuesi
Abstract: Despite multifunctional nanoparticles using for photothermal therapy can efficiently kill cancer cells, their further application is still hindered by the intrinsic high uptake in the reticuloendothelial system (RES) organs, causing the slow elimination from the body and potential toxicity to the body. Therefore, it is ideal to develop multifunctional nanoparticles which process the ability to effectively accumulate in tumors, while the nanoparticles can be rapidly excreted from the body via renal clearance after effective treatment. Herein, we report the multifunctional nanoparticles (FeTNPs) based on the coordination interaction of phenolic group and metal iron, which are composed of ferric iron, tannic acid (TA) and poly (glutamic acid)- graft -methoxypoly (ethylene glycol) (PLG- g -mPEG). FeTNPs exhibit the following highlighted features: (1) The effective accumulation in the tumor tissue is achieved based on EPR effect. (2) The dual photoacoustic (PA)/magnetic resonance (MR) imaging capacity can provide guidance for the photothermal therapy (PTT). (3) FeTNPs can be dynamically disassembled by deferoxamine mesylate (DFO) to accelerate elimination of the nanoparticles, thus reducing the potential toxicity for the body. The DFO triggered dynamic disassembling strategy may open a new avenue to overcome the dilemma between EPR effect and renal clearance.